How strongly did the 2007/08 oil price hike contribute to the subsequent recession? - Kai Carstensen; Steffen Elstner; Georg Paula (Center for Economic Studies and ifo Institute (CESifo), 2011)
In this paper we challenge the view that the oil price has lost its influence on economic activity after the mid-1980s. While we concede that typical VAR models put forward in the literature fail to identify oil price shocks that significantly affect aggregate production, we obtain clearly negative output and positive producer price effects of oil price hikes in a firm level analysis for which we exploit a unique microeconomic data set for Germany. Inspired by this finding, we aggregate the firm level information into a single indicator that signals in which periods the German economy was in a supply regime, i.e., in a situation when prices and production moved into opposite directions. Concentrating an otherwise standard VAR based search on these periods, we are able to identify an oil price shock that affects the German production even on the aggregate level. In a counterfactual analysis we show that the 2007/08 oil price hike contributed notably to the subsequent recession in Germany even though it was by far not the main driver.
Keywords: C30; E30; E32; 330; oil price shock; VAR model; micro data; Mineralölpreisschock; Konjunktur; VAR-Modell; Mikrodaten; Geschäftsklima; Schätzung; Deutschland